Semiology and neurophysiology of clonic seizures in children: a retrospective study - Hu, Qiao; Luo, Yuanyuan; Li, Tingsong; Hong, Siqi; Yuan, Ping; Jiang, Li (Frontiers in Neurology, 2025)
ObjectivesTo identify and quantify clonic seizures in children, we retrospectively reviewed the clinical symptoms and neurophysiology of them.MethodsData were obtained from 24 patients presenting with 34 clonic seizures, and their video-electroencephalography (EEG) recordings were examined for symptomatology and ictal EEG characteristics. Additionally, synchronous electromyography (EMG) data from 17 patients were analyzed.ResultsOur quantitative analysis demonstrated high diagnostic precision in lateralizing focal clonic seizures, with 90.9% exhibiting contralateral hemispheric concordance. The perirolandic region emerged as the predominant seizure-onset zone (62.85%), while paroxysmal rhythmic monomorphic activity constituted the most frequent ictal EEG pattern (72.72%). Semiological evaluation revealed preferential lower limb involvement at onset (38.23% of seizures) followed by upper limb manifestations (14.7%), with propagation patterns dominated by medial-to-lateral spread (63.63%) over purely lateral dissemination (36.36%). Neurophysiological profiling identified a mean EEG–EMG discharge latency of 115.88 msec. Notably, epilepsy represented the primary underlying etiology (83.83%), distinguishing pediatric clonic seizures from adult populations where structural lesions predominate.ConclusionThe lateralizing value, seizure-onset zone and EEG seizure pattern in childhood clonic seizures exhibited consistency with those observed in adults. Nonetheless, distinctions were noted in the initial affected body parts, latency, and etiology compared to adult cases. The delineated characteristics in this study could facilitate the recognition and assessment of clonic seizures during video-EEG monitoring in children.